PERANCANGAN SISTEM INFORMASI SIMPAN PINJAM DI KOPERASI HIKMAH CISAKTI CIGEULIS PANDEGLANG - Roni Surahman; Ratnanto Aditiarno (INFOKOM (Informatika & Komputer), 2020)
Current technological progress was progressively quick its developing. Along with perkembanganya therefore requirement will process data processing rapid fire and accurate beginning being felt by an organization or governance institution. One of that beginning feel requirement will process data processing rapid fire which is Co-op Hikmah Cisakti. In its data processing Hikmah Cisakti's Co-op stills to do registry ala in ledger, Unsecured arithmetic process and also installment be still manually been done, that thing gets to constrain deep data processing process, to it is required marks sense integrated information system deep its data processing that resulting information faster and accurateObservational method that is utilized is descriptive method which is method which just figure and boiling down various condition, situation or a variety variable. Development or information system approaching that is utilized in this Final Task utilize development method Waterfall . Meanwhile tool those are utilized in system scheme analysis is Flowmap, Context diagram, Flow's data diagram, ERD, Relationship table, meanwhile implementation of design of system is lingual pemograman Visual Basic 6.0 and SQL is server 2000 as database. Management information system makings this saving and lending gets to help Co-op performance especially at Saving And Lending part in do transactions with computerised system.Saving And Lending Management information system at A Cooperative Society Hikmah Cisakti is made for saving and lending transactions